PENGARUH IRIGASI DAN NAUNGAN TERHADAP PRODUKSI TANAMAN CABE (CAPSICUM ANNUM) PADA LAHAN BERPASIR DI PANTAI GLAGAH, YOGYAKARTA - Mawardi, Ikhwanuddin; Sudaryono, Sudaryono (Jurnal Hidrosfir Indonesia, 2008)
Coastal area is one of the marginal areas that is not suitable for agriculture field. However, bad quality of the area can be improved physically and chemically by adding some organic matters into the soil. Another factor that also plays an important role in improving the quality of sandy soil is weather, which consists of sun radiation, temperature, humidity, soil temperature, wind flow and rain fall. In order to obtain a good quality micro weather in a chili vegetation field, a cover may be placed above the vegetation to create a warm and wet micro weather which will free the vegetation from stress. Another important thing to attain success in productive agriculture is a certainty to get water or irrigation that can be engineered. Through those environmental engineering, an improvement on chili harvesting product has been achieved at Glagah Coast, West Progo, Yogyakarta.